THE INFLUENCE OF BAP TO IMPROVE OF SUNKIST GRAFTING - marpaung, intan purnama sari; Anggorowati, dini; hadijah, siti (Jurnal Sains Mahasiswa Pertanian, 2019)
This reasearch is aimed at improving BAP to sunkist grafting. This reasearch was conducted on March 7th, 2018 until June 4th, 2018 which in Husein Hamzah street, Pontianak, West Kalimantan. This reasearch design used Complete Randomized Design (CRD) with 5 treatment levels, which are 0 ppm, 50 ppm, 100 ppm, 150 ppm, and 200 ppm. Each treatment was repeated 5 times and each sample consisted of 5 samples, so that the total plant is 125. The variables observed in this reasearch included the percentage of survival, the increase of shoot length, the number of leaves, and the number of shoots. The results of this reasearch showed that there were no significant variables that influence of BAP to improving of Sunkist grafting.